2014
DOI: 10.1038/srep07206
|View full text |Cite
|
Sign up to set email alerts
|

Fast Response and High Sensitivity ZnO/glass Surface Acoustic Wave Humidity Sensors Using Graphene Oxide Sensing Layer

Abstract: We report ZnO/glass surface acoustic wave (SAW) humidity sensors with high sensitivity and fast response using graphene oxide sensing layer. The frequency shift of the sensors is exponentially correlated to the humidity change, induced mainly by mass loading effect rather than the complex impedance change of the sensing layer. The SAW sensors show high sensitivity at a broad humidity range from 0.5%RH to 85%RH with < 1 sec rise time. The simple design and excellent stability of our GO-based SAW humidity sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 58 publications
3
97
0
1
Order By: Relevance
“…For example, SAW devices have been reported that are responsive to hydrogen and carbon monoxide, 6 and moisture. 7,8 Huan et al 9 have very recently reported ZnO/glass humidity sensors with high sensitivity, exploiting a graphene oxide sensing layer, where the frequency response of the sensors was primarily caused by mass loading effects, which were also studied by Whitehead et al in graphene-quartz SAW devices. 10 Illumination of randomly stacked graphene flakes on lithium niobate (LiNbO 3 ) by 633 nm laser light 11 has been shown to modulate the SAW velocity, where this shift in the velocity was attributed to the increase in surface temperature resulting from optical energy absorbed in the graphene layer.…”
mentioning
confidence: 99%
“…For example, SAW devices have been reported that are responsive to hydrogen and carbon monoxide, 6 and moisture. 7,8 Huan et al 9 have very recently reported ZnO/glass humidity sensors with high sensitivity, exploiting a graphene oxide sensing layer, where the frequency response of the sensors was primarily caused by mass loading effects, which were also studied by Whitehead et al in graphene-quartz SAW devices. 10 Illumination of randomly stacked graphene flakes on lithium niobate (LiNbO 3 ) by 633 nm laser light 11 has been shown to modulate the SAW velocity, where this shift in the velocity was attributed to the increase in surface temperature resulting from optical energy absorbed in the graphene layer.…”
mentioning
confidence: 99%
“…Theoretical studies predict a range of rich physical phenomena arising from SAW-graphene interactions [14][15][16][17], and graphene's potential as an extraordinarily responsive sensing material [18] is being exploited for the development of SAW sensors. For example, SAW devices that are responsive to hydrogen and carbon monoxide [19], and moisture [20][21][22][23] have been reported. Acoustic charge transport has also very recently been reported in graphene [24,25], and we have investigated it in monolayer graphene, produced by chemical vapor deposition (CVD), and transferred onto lithium niobate SAW devices, both at room temperature [26], at low temperature [27], and under illumination [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they can be passive (no power source) and wireless (can be operated remotely) [16]. A large number of applications has been reported in the literature on SAW devices such as SAW chemical, pressure, and temperature sensors, as well as several other commercial applications [17][18][19][20][21]. In this paper, we report the detection of female Aedes mosquitoes in human habitations using a SAW sensor based on the ZnO/IDT/128º YX LiNbO 3 structure.…”
Section: Accepted Manuscriptmentioning
confidence: 94%